Non-Invasive Diagnostic Imaging in Kaposi Sarcoma Evaluation - Cantisani, Carmen; Di Guardo, Antonio; Ardigò, Marco; Suppa, Mariano; Gonzalez, Salvador; Longo, Caterina; Taliano, Alberto; Rovaldi, Emanuele; Cinotti, Elisa; Pellacani, Giovanni (Diagnostics (Basel), 2025)
Background and Clinical Significance: Kaposi sarcoma (KS) is a rare angio-proliferative mesenchymal tumor that predominantly affects the skin and mucous membranes but may involve lymph nodes and visceral organs. Clinically, it manifests as red-purple-brown papules, nodules, or plaques, either painless or painful, often with disfiguring potential. The diagnosis is traditionally based on clinical and histopathological evaluation, although non-invasive imaging techniques are increasingly used to support diagnosis and treatment monitoring. We report a case of HHV-8-negative Kaposi sarcoma evaluated with multiple non-invasive imaging modalities to highlight their diagnostic utility. Case Presentation: An 83-year-old man presented with multiple painful, violaceous papulo-nodular lesions, some ulcerated, on the lateral aspect of his left foot. Dermoscopy revealed the characteristic rainbow pattern. Dynamic Optical Coherence Tomography (D-OCT) allowed real-time visualization of microvascular abnormalities, identifying large serpentine and branching vessels with clearly delineated capsules. Line-field Optical Coherence Tomography (LC-OCT) showed irregular dermal collagen, vascular lacunae, and the presence of spindle cells and slit-like vessels. Histological analysis confirmed the diagnosis of Kaposi sarcoma, revealing a proliferation of spindle-shaped endothelial cells forming angulated vascular spaces, with red blood cell extravasation and a mixed inflammatory infiltrate. Conclusions: Non-invasive imaging tools, including dermoscopy, D-OCT, and LC-OCT, have emerged as valuable adjuncts in the diagnosis and monitoring of KS. These techniques enable in vivo assessment of vascular architecture and tissue morphology, enhancing clinical decision-making while reducing the need for immediate biopsy. Dermoscopy reveals polychromatic vascular features, such as the rainbow pattern, while D-OCT and LC-OCT provide high-resolution insights into vascular proliferation, tissue heterogeneity, and cellular morphology. Dermoscopy, dynamic OCT, and LC-OCT represent promising non-invasive diagnostic tools for the assessment of Kaposi sarcoma. These technologies provide detailed morphological and vascular information, enabling earlier diagnosis and more personalized management. While histopathology remains the gold standard, non-invasive imaging offers a valuable complementary approach for diagnosis and follow-up, particularly in complex or atypical presentations. Ongoing research and technological refinement are essential to improve accessibility and clinical applicability.